# SOLUTION: Find the sum: 8/15 + (-2/3) Find the sum: -3 1/4 + (-2 2/5) Find the difference: 5/8 - 3/4 Find the difference: -4/10 - (-1/6) Find the difference: -6 2/3 - 4 3/5

Algebra ->  Equations -> SOLUTION: Find the sum: 8/15 + (-2/3) Find the sum: -3 1/4 + (-2 2/5) Find the difference: 5/8 - 3/4 Find the difference: -4/10 - (-1/6) Find the difference: -6 2/3 - 4 3/5       Log On

 Ad: Mathway solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Equations Solvers Lessons Answers archive Quiz In Depth

 Question 334122: Find the sum: 8/15 + (-2/3) Find the sum: -3 1/4 + (-2 2/5) Find the difference: 5/8 - 3/4 Find the difference: -4/10 - (-1/6) Find the difference: -6 2/3 - 4 3/5 Any help will be appreciated! Thanks!Found 2 solutions by stanbon, checkley77:Answer by stanbon(60771)   (Show Source): You can put this solution on YOUR website!Find the sum: 8/15 + (-2/3) = (8/15)-(10/15) = -2/15 --------------------------------------------------------- Find the sum: -3 1/4 + (-2 2/5) = (-13/4)-(12/5) = (-65/20)-(48/20) = -113/20 --------------------------------------------------------- Find the difference: 5/8 - 3/4 = (5/8)-(6/8) = -1/8 --------------------------------------------------------- Find the difference: -4/10 - (-1/6) = (-12/30)+(5/30) = -7/30 --------------------------------------------------------- Find the difference: -6 2/3 - 4 3/5 = (-20/3)-(23/5) = (-100/15)-(69/15) = -169/15 ========================================================== Cheers, Stan H. Answer by checkley77(12569)   (Show Source): You can put this solution on YOUR website!Find the sum: 8/15 + (-2/3) 8/15-10/15=-2/15 ans. Find the sum: -3 1/4 + (-2 2/5) (-12+1)/4-(2*5+2)/5 -11/4-(10+2)/5 -11/4-12/5 (-11*5-12*4)/4*5 (-55-48)/20 -103/20 ans. Find the difference: 5/8 - 3/4 5/8-6/8=-1/8 ans. Find the difference: -4/10 - (-1/6) -4/10+1/6 (-4*5+1*3)/30 (-20+3)/30 -17/30 ans. Find the difference: -6 2/3 - 4 3/5 (-6*3+2)/3-(4*5+3)/5 (-18+2)/3-(20+3)/5 -16/3-23/5 (-16*5-23*3)/(3*5) (-80-69)/15 149/15 ans.